DEFEAT IN THE ARENA. (April 2019) - Coleman, Kathleen M.
Abstract : Everybody in life wants to win. At its most basic, this must stem from the survival instinct: in a battle against predators, winning means survival; defeat means death. In a social context, however, obviously not everyone can win, and we have to learn to accommodate defeat, whether our own or that of others. Hence, in a competitive society, defeat presents a challenge. Usually, if an observer sympathizes with the defeated, there is an impulse to dress up the defeat in various guises; or, if the defeated party is scorned, the defeat is presented in the most humiliating terms possible. In a gladiatorial context, the attitudes of the observer, not to mention the gladiators themselves, are hard to recover. Recent work has focused on the 'affective dispositions' of the spectators, drawing analogies with modern combat sports. Yet, modern spectators do not have to decide whether the defeated party deserves to live or die, whereas, for a Roman spectator, defeat was to be calibrated on a scale of life and death. The ancient protagonists themselves will obviously share impulses with their modern equivalents, although, when the contest is potentially fatal, the drive to win must take on an urgency surpassing pure ambition. When a modern athlete dies on the sports field or in the boxing ring, it is an accident, however tragic, whereas a gladiator who lost a fight could suffer the penalty of losing his life as well. Defeat was in deadly earnest.